PENGARUH LINGKUNGAN KELUARGA TERHADAP MOTIVASI BELAJAR SOSIOLOGI SISWA SMA ISLAM HARUNIYAH PONTIANAK - Syukri, Akhmad; Rustiyarso, Rustiyarso; Salim, Izhar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to determine the effect of: Family Environment on Motivation to Study Sociology in class XI of Haruniyah Islamic High School 2017/2018 Academic Year. The subjects of this study were 70th grade students of Social Sciences at SMA Islam Haruniyah. Data collection techniques using observation, documentation and questionnaire / questionnaire methods. Observation methods to reveal family environment variables, documentation methods and questionnaire methods are used to reveal the variables of learning motivation. Instrument testing was carried out at Islamic High School Haruniyah with N = 40. Test the validity of the instrument using Product Moment correlation, and reliability testing using Alpha Cronbach's formula. Analysis prerequisite test consists of linearity test and multicollinearity test. Data analysis used is a simple regression analysis technique for hypotheses (X - Y). The results showed that: The influence of the family environment on learning motivation was obtained by the price of the correlation correlation rxy of 0.312 at N = 40 and the price of the determination coefficient r2xy of 0.098. . Sig value. 0.050 <0.05 significance level. The magnitude of the Adjusted R Square coefficient = 0.74, which means that the influence of variable X on variable Y is 7.8% and the remaining 92.2% is influenced by variables other than family environment variables.Â Â Keywords: Family Environment, Learning Motivation, Sociology LessonsÂ